HISTORIOGRAFI MASA KEEMASAN KODIFIKASI HADIS ABAD KETIGA HINGGA KELIMA HIJRIAH (Analisis Historis dan Metodologis Kodifikasi Hadis Perspektif Sunni) - Qhoirin Anisa; Muhammad Muqla Syauqy Tamam; Maghfiroh; Hakami Mundziri Sastra; Isnel Arfen Azizah; Anisa, Qhoirin; Tamam, Muhammad Muqla Syauqy (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract This study analyzes the historiography of hadith codification from a Sunni perspective during the golden age of hadith compilation, namely the third to fifth centuries of the Hijri era. The primary focus is on the historical and methodological development of hadith codification, encompassing the stages of collection, criticism, and compilation of hadith books. This period was marked by the emergence of hadith disciplines such as al-Jarh wa al-Ta'dil and Ilal al-Hadis, as well as the formation of key books such as Kutub al-Sittah. The study also highlights the influence of Sahih al-Bukhari in establishing the criteria for authenticity of hadith, which became a reference for subsequent scholars. Using a library research approach with descriptive analysis, this study emphasizes the importance of the Sunni perspective in maintaining the purity of hadith amidst controversies over Islamic sects. The results indicate that the third century of the Hijri era marked the peak of codification, with significant contributions to the preservation of Islamic tradition. Keywords: Bukhari; Golden; Hadith; Sunni.